Solvent triggering structural changes for two terbium-based metal–organic frameworks and their photoluminescence sensing. Issue 31 (19th March 2020) - Yue, Dan; Wang, Yanyan; Chen, Dong; Wang, Zhenling
Abstract : TbPDBA-8 and TbPDBA-9 have been obtained based on the same ligand, and have different structures and luminescence properties. Abstract : Two terbium-based metal–organic frameworks (TbPDBA-8 and TbPDBA-9) based on the same ligand have been successfully obtained. Only by changing the solvent content, TbPDBA-9 can be transformed into TbPDBA-8, and the addition of sodium formate will accelerate the process. They showed the detection performance of ascorbic acid and H2 O content respectively.